Assessment of illegal forest activities on plant diversity in Tano Offin globally significant biodiversity area (GSBA) in the Nkawie Forest District, Ghana - Opare Addo, Yaw Michael (2014)
A thesis submitted to the Department of Environmental Science, Kwame Nkrumah University of Science and Technology, Kumasi in partial fulfillment of the requirements for the Master of Science Degree in Environmental Science.